In-depth analysis of patient-clinician cell phone communication during the WelTel Kenya1 antiretroviral adherence trial. - Mia L van der Kop; Sarah Karanja; Lehana Thabane; Carlo Marra; Michael H Chung; Lawrence Gelmon; Joshua Kimani; Richard T Lester (PLoS ONE, 2012)
The WelTel Kenya1 trial demonstrated that text message support improved adherence to antiretroviral therapy (ART) and suppression of HIV-1 RNA load. The intervention involved sending weekly messages to patients inquiring how they were doing; participants were required to respond either that they were well or that there was a problem.1) Describe problems participants identified through mobile phone support and reasons why participants did not respond to the messages; 2) investigate factors associated with indicating a problem and not responding; and 3) examine participant perceptions of the intervention.Secondary analysis of WelTel Kenya1 trial data.Reasons participants indicated a problem or did not respond were extracted from the study log. Negative binomial regression was used to determine participant characteristics associated with indicating a problem and non-response. Data from follow-up questionnaires were used to describe participant perceptions of the intervention.Between 2007 and 2009, 271 participants generated 11,873 responses; 377 of which indicated a problem. Health issues were the primary reason for problem responses (72%). Rural residence (adjusted incidence rate ratio [IRR] 1.96; 95%CI 1.19-3.25; p=0.009 and age were associated with indicating a problem (adjusted IRR 0.63 per increase in age group category; 95%CI 0.50-0.80; p<0.001). Higher educational level was associated with a decreased rate of non-response (adjusted IRR 0.81; 95%CI 0.69-0.94; p=0.005). Of participants interviewed, 62% (n=129) stated there were no barriers to the intervention; cell phone issues were the most common barrier. Benefits included reminding patients to take medication and promoting a feeling that "someone cares".The WelTel intervention enabled frequent communication between clinicians and patients during the WelTel Kenya1 trial. Many patients valued the service for the support it provided, with health-related concerns comprising the majority of problems identified by participants. Few sociodemographic characteristics were associated with participant engagement in the intervention.